2000
DOI: 10.1016/s0022-2275(20)32365-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apolipoprotein A-IV genotype and dietary fat on cholesterol absorption in humans

Abstract: We investigated the effect of the A-IV-2 allele, which encodes a Q360H substitution in apolipoprotein (apo) A-IV, and dietary fat on cholesterol absorption in humans. In three separate studies we compared fractional intestinal cholesterol absorption between groups of subjects heterozygous for the A-IV-2 allele (1/2) and homozygous for the common allele (1/1) receiving high cholesterol ( ϳ 800 mg/day) diets with different fatty acid compositions. All subjects had the apoE 3/3 genotype. There was no difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 54 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, it is not known whether neural effects of apoA-IV affect gastric emptying in humans or whether apoA-IV polymorphisms could modulate its effect on gastrointestinal function. We have shown that the A-IV-2 allele reduces the efficiency of cholesterol absorption in subjects consuming a polyunsaturated fat diet (40), which suggests that apoA-IV may play a role in modulating chylomicron assembly. However, intestinal lipid absorption is grossly normal in apoA-IV knock-out mice (53); hence, the function of apoA-IV in chylomicron synthesis must be an accessory one.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nonetheless, it is not known whether neural effects of apoA-IV affect gastric emptying in humans or whether apoA-IV polymorphisms could modulate its effect on gastrointestinal function. We have shown that the A-IV-2 allele reduces the efficiency of cholesterol absorption in subjects consuming a polyunsaturated fat diet (40), which suggests that apoA-IV may play a role in modulating chylomicron assembly. However, intestinal lipid absorption is grossly normal in apoA-IV knock-out mice (53); hence, the function of apoA-IV in chylomicron synthesis must be an accessory one.…”
Section: Discussionmentioning
confidence: 89%
“…This allele encodes a Q360H substi-tution (33) that significantly increases the lipid affinity (34), lecithin:cholesterol acyltransferase activation (34), and plasma residence time (35) of the apoA-IV-2 isoprotein. Recently, several studies have observed that the A-IV-2 allele affects the plasma lipoprotein response to dietary fat and cholesterol (36)(37)(38)(39), and may also modulate the efficiency of intestinal cholesterol absorption (40).…”
mentioning
confidence: 99%
“…Several mutations have also been described in APOA-IV, although the two most common are a T347S and Q360H aminoacid substitutions (Lohse, Kindt, Rader, & Brewer, 1990a, 1990b. These mutations have been associated with altered lipid profile, including triglyceride clearance, cholesterol absorbance and overall variability of HDL particles (Gomaraschi et al, 2010;Hockey, Anderson, Cook, Hantgan, & Weinberg, 2001;Jansen, Lopez-Miranda, et al, 1997;Weinberg et al, 2000). Although one study indicated a genetic association between the APOA-IV Q360T polymorphism and AD, two other reports failed to confirm this finding (Csaszar, Kalman, Szalai, Janka, & Romics, 1997;Ji, Urakami, et al, 1999;Merched, Xia, Papadopoulou, Siest, & Visvikis, 1998).…”
Section: Apolipoproteinsmentioning
confidence: 99%